Synthesis and Characterization of Cu2CdSnS4 Quaternary Alloy Nanostructures - Al-Douri, Yarub; Odeh, Ali Abu; Johan, Mohd Rafie; Chowdhury, Zaira Zaman; Rafique, Rahman Faizur; Reshak, Ali Hussain; Voon, Chun Hong (Electrochemical Science Group, 2018)
Cu2CdSnS4 (CCTS) quaternary alloy nanostructure is an important material of enhancing the sensors effectiveness. CCTS nanostructures have been synthesized using ultrasonic and deposited on SiO2/Si substrate using sol-gel method and under annealing temperature; 400 oC. Structural optical, topographical and morphological properties of CCTS were explored using Ultraviolet-visible spectroscopy, X-ray diffraction (XRD), atomic force microscopy (AFM) and scanning electron microscopy (SEM), respectively. Interdigitated electrodes (IDEs) have been manufactured via deposited silver on CCTS/SiO2/Si substrate via a physical vapor deposition and hard mask. Electrical properties of fabricated IDEs are further evaluated as a function of voltage and frequency. The proposed IDEs can be used in subsequent studies to develop a biological sensor capable of detecting the DNA for many types of diseases in order to facilitate the combating and eradicating. The resulted values are in agreement with others.